Comparison Between Dynamic Neuromuscular Stabilization Breathing Exercises and Pilates Exercises in Young Overweight Individuals with Activity-Related Breathlessness - D. Rawal, Aishwarya; Sagar, Javid H.; Rayjade, Amrutkuvar S. (Journal of Neonatal Surgery, 2025)
Method: The study was conducted on 80 young overweight individuals matching the inclusion criteria from college going students who were given intervention for 3 days a week per 6 weeks. Pre-intervention assessment was done on day 1 and post intervention assessment was done after 6 weeks. Through randomized selection patients were divided into two groups, Group A DNS breathing exercises and Group B Pilates Exercises. Outcome measures: mMRC scale, Harward Step Test, Diaphragm MMT was assessed at baseline and after 6weeks day post-intervention. Result: Both the Groups DNS breathing exercises and Pilates exercises demonstrated significant improvement in terms of reducing activity related breathlessness. Between-group analyses showed that group A DNS was more effective than group Pilates exercises in improving aerobic capacity, and group B Pilates exercises was more effective than group A DNS breathing exercises in improving Diaphragm muscle strength. Conclusion: DNS breathing exercises and Pilates exercises demonstrated significant improvement in terms of reducing activity related breathlessness. The group A DNS was more effective than group Pilates exercises in improving aerobic capacity, and group B Pilates exercises was more effective than group A DNS breathing exercises in improving Diaphragm muscle strength.